Cover Image, Volume 76, Issue 7. Issue 7 (7th June 2020) - Li, Dan‐Ting; Dai, Yi‐Ting; Chen, Xuan; Wang, Xin‐Qiu; Li, Ze‐Dong; Moussian, Bernard; Zhang, Chuan‐Xi
Abstract : The cover image is based on the Research Article Ten fatty acyl‐CoA reductase family genes were essential for the survival of the destructive rice pest, Nilaparvata lugens by Dan‐Ting Li et al., https://doi.org/10.1002/ps.5765 . Abstract : The cover image is based on the Research Article Ten fatty acyl‐CoA reductase family genes were essential for the survival of the destructive rice pest, Nilaparvata lugens by Dan‐Ting Li et al., https://doi.org/10.1002/ps.5765 .